Strategi Upaya Mitigasi Bencana Kebakaran Hutan di Kalimantan Barat Berbasis Kebiasaan Setempat - Mandayu, Claudia Olla; Wiyatiningsih; Utomo, Gregorius Sri Wuryanto Prasetyo (ATRIUM: Jurnal Arsitektur, 2024)
Title: Strategy for Mitigating Forest Fire Disasters in West Kalimantan Based on Local Customs Forest and land fires (karhutla) are annual disasters in West Kalimantan. Forest and land fires are caused by two factors, namely natural factors and human factors. At the same time, the Dayak community practices land clearing by burning forests. This study aims to identify strategies carried out by the Dayak Tribe in efforts to mitigate forest fire disasters based on local customs. The research method used is a descriptive approach with a disaster adaptation theory framework based on local beliefs to prove the hypothesis. The study results indicate that the Dayak community has anticipated the karhutla disaster during land clearing with disaster mitigation strategies based on local customs.